Interior Space Reconstruction Design Based on Human Settlement Behavior Analysis - Yang, Jiachen; Yuan, Lin; Wang, Xiang (Journal of Social Science and Humanities, 2024)
The renovation of residential space based on the analysis of human settlements behavior is an important method to improve the quality of old houses. Especially for small houses, in the limited space, it is necessary to optimize the spatial layout, enhance the function of storage space, and improve the user's living experience, which needs to start from the user's individual needs and psychological level, and explore the method of design and transformation. Taking residential housing in Beijing as an example, this paper analyzes and investigates the current situation of indoor scenes, layouts and interfaces, and focuses on the methods of residential space transformation through the application of ergonomics and mixed reality technology.